Enhancing Students’ Self-Determination through a Local Instruction Theory in Mathematics - Iryana Muhammad; Al Jupri; Kusnandi Kusnandi; Siti fatimah (SJME (Supremum Journal of Mathematics Education), 2026)
The struggle of junior high school students to grasp One-Variable Linear Inequalities often stems from a lack of internal motivation and self-determination. Addressing this challenge, the present study explores the potential of a Local Instruction Theory (LIT) based learning design to foster students’ self-driven engagement in mathematics. Conducted in two instructional cycles with students in Lhokseumawe, Indonesia, the study employed a qualitative approach using a 24-item Likert-scale questionnaire measuring autonomy, competence, relatedness, and active willingness to learn. The results of the self-determination questionnaire analysis showed clear positive changes. The total subjects in this study was 57 students, of whom 31 participated in the first experimental phase (TE-1). Only 16% of students showed high self-determination. In contrast, in the second phase (TE-2) with 26 students as subjects in the first experimental phase (TE-1), only 16% of students demonstrated high self-determination. In contrast, in the second phase (TE-2), In the second phase (TE-2), the proportion of students with high self-determination increased from 16% to 35%, while the medium category decreased from 77% to 62% and the low category declined from 6% to 4%. These results highlight the promise of contextual, structured instruction supported by well-designed learning materials in cultivating students’ intrinsic motivation. More broadly, this study offers a compelling direction for designing affective-centered math instruction. Future research is encouraged to integrate multiple data sources and expand LIT implementation across diverse mathematical domains